2019
DOI: 10.1103/physreva.99.020301
|View full text |Cite
|
Sign up to set email alerts
|

Entangling protocols due to non-Markovian dynamics

Abstract: It is widely spread in the literature that non-Markovianity (NM) may be regarded as a resource in quantum mechanics. However, it is still unclear how and when this alleged resource may be exploited. Here, we study the relationship between NM and quantum optimal control under the objective of generating entanglement within M non-interacting subsystems, each one coupled to the same non-Markovian environment. Thus, we design a variety of entangling protocols that are only achievable due to the existence of the en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Memory effect, i.e., the temporary revival of previously leaked information, is one of the fascinating topics in this fields [1]. It is considered a signature of the non-Markovianity firstly [2][3][4][5][6][7][8][9][10], then became a vital method for manipulating quantum resources [7,8] such as entanglement [11][12][13][14][15][16], quantum interferometric power [17], temporal steering [18], quantum coherence, correlations [10], and quantum Fisher information (QFI) [9,19]. With the booming of technologies of control and manipulation open quantum systems [20][21][22][23][24][25][26][27][28], applications in ultracold atomic gases [24,25], quantum speed limit [29][30][31], algorithms [32,33], and thermal machines [34,35] are under intensive studies in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Memory effect, i.e., the temporary revival of previously leaked information, is one of the fascinating topics in this fields [1]. It is considered a signature of the non-Markovianity firstly [2][3][4][5][6][7][8][9][10], then became a vital method for manipulating quantum resources [7,8] such as entanglement [11][12][13][14][15][16], quantum interferometric power [17], temporal steering [18], quantum coherence, correlations [10], and quantum Fisher information (QFI) [9,19]. With the booming of technologies of control and manipulation open quantum systems [20][21][22][23][24][25][26][27][28], applications in ultracold atomic gases [24,25], quantum speed limit [29][30][31], algorithms [32,33], and thermal machines [34,35] are under intensive studies in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a memory environment will make the information flow back from the environment to the system, and this leads to non-Markovian dynamics. Non-Markovian dynamics has attracted a great deal of attention from researchers in both theoretical and experimental studies because of its important role in quantum state engineering, quantum control, and quantum information processing [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. One important aspect of non-Markovian dynamics is its effect on the entanglement generation of the system’s quantum states.…”
Section: Introductionmentioning
confidence: 99%
“…However, in many solid-state devices and other systems this assumption breaks down [8][9][10][11][12] so one cannot use simple time-local density matrix equations of motion. In addition to non-Markovianity being common, it can be desirable [13][14][15][16][17][18][19][20][21][22][23][24]: it has been shown that non-Markovianity of open quantum systems can lead to higher fidelity of quantum operations due to the possible information backflow from the environment to the system. The simulation of general non-Markovian open quantum systems is, however, a computationally challenging task, which hampers progress on the design of optimal control procedures.…”
mentioning
confidence: 99%